THE EFFECT OF (LIST - GROUP - SIGN) STRATEGY ON THE ACHIEVEMENT OF FIFTH-GRADE STUDENTS IN CHEMISTRY - Fatima Salem Jaber, Mushriq Mohammad mujweal, Abbas HussainMugheer (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The research aims to identify the impact of (list - group - sign) strategy in the collection of students grade V Bio - substance chemistry , and to verify the goal the researcher set a zero hypothesis that states " There is no statistically significant difference at the level of significance (0.05) between the average scores of students of the experimental group who will study according to (list - group - sign) strategy and the average score Students of the control group who will study according to the usual method of testing the achievement of the chemistry subject", and in order to investigate them his experience applied in the classroom the second of the year school(2019-2020) m, formed the research sample of) 40 )student of the students grade V bio in junior high Was distributed randomly into two groups of(20) student of each group, it has been rewarded with the two groups in the following variables: chronological age, IQ test , score the second course of the previous academic year in material chemistry , and test the previous information, and in the light of The relative importance of the content and behavioral purposes, an achievement test consisting of(40) items was constructed of (30) items of multiple choice type and(10) paragraphs of the type of essay questions , the researcher has investigated the characteristics of the psychometric test of the test , the experiment continued to apply(10) as I sell , and at the end of the experiment summative test was applied to the two groups , then analyzed the results showed the superiority of the students of the experimental group of Latte lesson according)List-group-Sign) strategy on the control group of the Latte studied the usual way in the academic achievement variable.